The Symbols of Isolation In Laurie Halse Anderson’s Speak - Ridho Pratama Satria; Eva Najma; Seswita Seswita (English Department, Faculty of Humanities, Andalas University, 2022)
This research discusses the role of symbols found in Laurie Halse Anderson’s Speak. The writers apply New Criticism as the way to find the meaning from those symbols. The writers find three important symbols in the story, they are Melinda’s tree painting, mirror, and Melinda’s lips and mouth condition. Anderson puts those symbols in the story in order to strengthen the salvation from the isolation as the solid theme for Speak.